O comércio e a cidade:novas territorialidades urbanas - Geisa Daise Gumiero Cleps (Sociedade & Natureza)
Studying the trade history we can see tha it always been on a strategic place into the city space, being its function to produce and to take advantage of the ammount of population. Trough this meaning, location is considered as a pre-requisite for any commercial stablishment. On the other hand, the ways of trading also creates new centralities connected to the nature of market trading. It can be said that the commercials retail development happened on a spontaneous way as a manifestation of the differents needs of the differents societies on differents moments. This way, the trade has changed from a social function to a more economic function, which has been inventing and adopting new tecnics of commercialization, expanding, incorporating and bringing out chages on trading relationships, and mostly, on where it occurs. Currently, in case of important transformations that need bigger with the world productive system, there are new commercial modalities that need bigger areas to be installed. Searching new spaces, whick were considered perepheral before, important trading webs create new urban centralities. The place where they install occurs a space valuation. Therefore, this work has as it purpose to analyse the mains transformations that have happened on urban spaces, with the instalation of new commercial stablishments, which create new consumptions spaces, new ideas, social values, at last, new centralities.